2005
DOI: 10.1002/cncr.20976
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative serum C‐reactive protein on the prognosis of patients with hepatocellular carcinoma

Abstract: BACKGROUNDThe authors evaluated the significance of the preoperative serum C‐reactive protein (CRP) level as a prognostic indicator in patients with hepatocellular carcinoma (HCC).METHODSOne hundred forty‐one patients who underwent curative resection for HCC were reviewed retrospectively. Clinicopathologic variables were compared between patients with serum CRP levels ≥ 1.0 mg/dL (n = 22 patients; the CRP‐positive group) and patients with serum CRP levels < 1.0 mg/dL (n = 119 patients; the CRP‐negative grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
205
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(221 citation statements)
references
References 35 publications
14
205
1
Order By: Relevance
“…Recent studies have showed that the preoperative elevated serum CRP level is an independent and significant predicative indicator of poor prognosis and early recurrence in patients with HCC (Hashimoto et al, 2005;Sieghart et al, 2013). However, SAA is superior to CRP for detecting inflammation resulting from viral infections, kidney transplantation, Crohn's disease, and ulcerative colitis (Yamada, 1999), and therefore SAA is probably more useful for detecting slight elevations in systemic or chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have showed that the preoperative elevated serum CRP level is an independent and significant predicative indicator of poor prognosis and early recurrence in patients with HCC (Hashimoto et al, 2005;Sieghart et al, 2013). However, SAA is superior to CRP for detecting inflammation resulting from viral infections, kidney transplantation, Crohn's disease, and ulcerative colitis (Yamada, 1999), and therefore SAA is probably more useful for detecting slight elevations in systemic or chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of serum CRP is a common feature in patients with malignancies which has been found to be adversely prognostic, with patients having elevated CRP levels (Nozoe et al, 1998;Nakanishi et al, 2002;Shimada et al, 2003;Hashimoto et al, 2005). Growing evidence suggests prognostic importance because increased CRP levels are associated with the production of cytokines from tumour cells (Kurzrock, 1997;Legouffe et al, 1998, Yamamura et al, 1998.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the prognostic value of baseline biological markers including high levels of b2-microglobulin (B2-M), lactate dehydrogenase (LDH), and serum albumin (Bataille et al, 1992), elevations of serum C-reactive protein (CRP) have been consistently associated with a poor prognosis in myeloma (Tienhaara et al, 1994;Kaneko et al, 2002;Terpos et al, 2003). Several studies regarding the role of preoperative CRP as a predictive indicator for the malignant potential and prognosis in various other cancers have been published (Nozoe et al, 1998;Nakanishi et al, 2002;Shimada et al, 2003;Hashimoto et al, 2005). However, the prognostic significance based on preoperative CRP has not been clarified for myeloma patients, yet.…”
mentioning
confidence: 99%
“…In fact, several studies have reported a prognostic value of elevated CRP levels in different types of cancer [8][9][10] including resectable HCC. [11][12][13] In this study we investigated the prognostic value of CRP levels in nonsurgical HCC patients with respect to the BCLC classification.…”
mentioning
confidence: 99%